2013
DOI: 10.3389/fncir.2013.00077
|View full text |Cite
|
Sign up to set email alerts
|

Tonotopic and localized pathways from primary auditory cortex to the central nucleus of the inferior colliculus

Abstract: Descending projections from the cortex to subcortical structures are critical for auditory plasticity, including the ability for central neurons to adjust their frequency tuning to relevant and meaningful stimuli. We show that focal electrical stimulation of primary auditory cortex in guinea pigs produces excitatory responses in the central nucleus of the inferior colliculus (CNIC) with two tonotopic patterns: a narrow tuned pattern that is consistent with previous findings showing direct frequency-aligned pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 79 publications
2
42
0
1
Order By: Relevance
“…In addition to the divergent anatomy shown in ascending pathways, there is also evidence that descending projections differentially affect regions along the isofrequency laminae of the ICC. A recent study demonstrated that electrical stimulation of A1 elicits descending excitatory activation in the caudal-and-medial regions within an ICC lamina but with little or no activation within the rostral-and-lateral regions (Markovitz et al 2013). Combined with the robust and precise activation properties of the rostral pathway that projects up to A1, these findings suggest that the rostral pathway may serve as the main ascending auditory pathway, whereas the caudal pathway, at least within the midbrain, may serve a more modulatory role for sound processing.…”
Section: A Dual Lemniscal Organizationmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the divergent anatomy shown in ascending pathways, there is also evidence that descending projections differentially affect regions along the isofrequency laminae of the ICC. A recent study demonstrated that electrical stimulation of A1 elicits descending excitatory activation in the caudal-and-medial regions within an ICC lamina but with little or no activation within the rostral-and-lateral regions (Markovitz et al 2013). Combined with the robust and precise activation properties of the rostral pathway that projects up to A1, these findings suggest that the rostral pathway may serve as the main ascending auditory pathway, whereas the caudal pathway, at least within the midbrain, may serve a more modulatory role for sound processing.…”
Section: A Dual Lemniscal Organizationmentioning
confidence: 99%
“…These anatomic features have been shown to be reliable and consistent for normalizing brains across animals in previous studies from our laboratory (Markovitz et al 2012(Markovitz et al , 2013. The laminae were approximated by creating a plane orthogonal to the average insertion angle of all best-fit lines of the array placements.…”
Section: Histology and Midbrain Reconstructionsmentioning
confidence: 99%
“…The thalamic is highlighted for its essential role in sending acquired auditory information to the amygdala and/or signal association during learning (Weinberger, 1998;Maren and Quirk, 2004;Sigurdsson et al, 2007). The auditory cortex receives attention as the highest auditory processing center and for its ability to direct subcortical functional remodeling Perrot et al, 2006;Nunez and Malmierca, 2007;Yan and Ehret, 2002;Luo et al, 2008;Suga, 2012;Markovitz et al, 2013Slater et al, 2013Mellott et al, 2014). Our data show here that frequency-specific plasticity was induced in both the MGBv and AI following a bottom-up direction from the ICc (Figs.…”
Section: Discussionmentioning
confidence: 63%
“…These corticofugal projections may influence plastic changes within the ICC, since there have been numerous studies showing that frequency tuning of ICC neurons can be finely shifted toward those of electrically stimulated AI neurons (Yan and Suga, 1998;Yan et al, 2005;Xiong et al, 2009). A more recent study also showed that electrical stimulation of AI neurons could cause extensive suppression of excitability of neurons in the ICC when paired with broadband noise stimulation (Markovitz et al, 2013). Less is known about corticofugal fibers that originate from non-AI cortical regions and target the ICC.…”
Section: Introductionmentioning
confidence: 97%